EFEKTIVITAS PENGGUNAAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN PEMBELAJARAN FIKIH DI MIN 2 PADANGSIDIMPUAN - Harahap, Efridawati (DIRASATUL IBTIDAIYAH, 2024)
Learning fiqh plays an important role in shaping religious understanding and practice for Muslims, especially children as the next generation of Islam. Often the achievement of teacher-student communication is not complex regarding important topics of Islamic jurisprudence. Conventional approaches to learning that rely on verbal lectures, reading texts, are often not enough to facilitate optimal understanding. This research aims to evaluate the effectiveness of using audio-visual media in improving fiqh learning among students. This research method uses literature study, research design, development of learning materials and data analysis. The results of this research indicate that the use of audio-visual media effectively increases students' understanding of fiqh concepts by presenting the material visually and auditively. Apart from that, audio-visual media also helps strengthen student information retention, increase involvement in the learning process, support various learning styles, encourage student creativity in expressing student understanding. Thus, the integration of audio-visual media in fiqh learning can be an effective strategy in improving student learning outcomes. This research provides a strong foundation for the development of more innovative curriculum and teaching methods in the context of fiqh learning.